Exploring the importance of the works of Johann Sebastian Bach: Pedagogical perspectives and the emotional response of listeners - Morgan, Neil; O’Neill, Katherine (Frontiers in Education, 2023)
Music education in the United Kingdom has long been centred on the study of historic European classical music. Many studies within the field of Music Psychology have investigated the various ways in which people respond to Western Art Music, and how those responses may differ in accordance with the listening context, but very few have examined the effect of music by specific composers. Bach’s music is still performed regularly around the world—arguably more so than any other composer—and continues to be regarded as essential repertoire by instrumental teachers across many disciplines. This study sought to investigate the potential reasons for this from the perspective of pedagogic value and listener response. A mixed-methods approach was adopted, incorporating semi-structured interviews with music educators alongside a listening experiment in which participants rated their emotional responses to a selection of pieces by Bach, Beethoven and Mozart. A reflexive thematic analysis was used to present an apologia for the continued propagation of Bach’s music in mainstream education, and listeners’ emotional responses were measured using a standardised scale. Additional ratings for valence, arousal, familiarity and overall enjoyment were also gathered from each participant. Results indicate a statistically significant relationship between the music of specific composers and some emotion categories. These findings could lend support to the continued hagiolatry of J. S. Bach in music education, in spite of the welcome drive towards the diversification of the curriculum.